2019
DOI: 10.5539/jas.v11n15p125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulp, Sugar and Maltodextrin Addiction in the Formulation of Kiwi Jellies With Lemon Grass Tea

Abstract: The jellies constitute an important alternative for the processing of fruits, adding greater economic and nutritional value. The objective of this study was to evaluate the effects of different concentrations of pulp, sugar and maltodextrin on the physical-chemical and textural characteristics of kiwifruit jelly with lemon grass tea. Factorial design 23 was used with 3 replicates at the central point, resulting in 11 experiments with variation of sugar percentages (30, 40 and 50%), pulp (50, 60 and 70%) and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…The moisture content can also change in particle size and morphological differences [ 73 ]. Foods that have a moisture content of more than 20% and a higher water activity of 0.60 are subject to deterioration processes caused by molds and yeasts [ 74 ]. The values found for the moisture content of 6.6% ± 0.06 and water activity 0.25 ± 0.007 were low and indicate a good drying process [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content can also change in particle size and morphological differences [ 73 ]. Foods that have a moisture content of more than 20% and a higher water activity of 0.60 are subject to deterioration processes caused by molds and yeasts [ 74 ]. The values found for the moisture content of 6.6% ± 0.06 and water activity 0.25 ± 0.007 were low and indicate a good drying process [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the jellies in both formulations, presented average levels of soluble solids close to 65 ºBrix, contents that are usually found in conventional fruit jellies (62 °Brix) (Barros et al, 2019). However, due to reduced sugar content in candy formulations, soluble solids showed reduced values, ranging from 59 to 60 ° Brix.…”
Section: Physicochemical Characterizationmentioning
confidence: 81%
“…It is observed that the average of the values determined for the humidity of the jellies, even though different between formulations (p ≤ 0,05), are within the range found for most fruit jellies. These values being also according to the quality standard established by the Brazilian legislation (Brazil, 1978), which indicates the maximum humidity content for fruit jellies lower to 38% (Barros et al, 2019). For paste candies this parameter did not vary between the different formulations.…”
Section: Physicochemical Characterizationmentioning
confidence: 90%
“…Na produção de geleia, a concentração da mistura permite a redução da atividade da água, permitindo maior estabilidade microbiológica ao produto e redução da carga microbiana, o que permite aumentar o prazo de validade (BARROS et al, 2019). A geleia é considerada como o segundo produto em importância comercial na indústria de conserva de frutas brasileiras e apresentam um mercado promissor (RIBAS et al, 2017).…”
Section: Fundamentação Teóricaunclassified